Draft Genome Sequences of Gammaproteobacterial Methanotrophs Isolated from Marine Ecosystems - Flynn, James D. (Genome Announc, 2016)
The genome sequences of Methylobacter marinus A45, Methylobacter sp. strain BBA5.1, and Methylomarinum vadi IT-4 were obtained. These aerobic methanotrophs are typical members of coastal and hydrothermal vent marine ecosystems.